Maternal Expansions of Child Language Relate to Growth in Children's Vocabulary. Issue 4 (1st October 2016) - Taumoepeau, Mele
ABSTRACT: Using multi-level growth modeling, we examined the effect of several measures of maternal input on growth in children's word types from 15–54 months. Mothers and children engaged in a picture description task ( N = 77) at 15, 24, 33, and 54 months; the frequency of children's observed word types at each wave was coded and additional independent measures of productive and receptive language were assessed at 24 months, and receptive language at 54 months. Mother language was coded for MLU, word types, and partial repetitions at four time points, and expansions at two timepoints. All measures of input, except for partial repetitions, contributed significantly to variance in children's word type growth over this period. The percentage of utterances that mothers expanded between the ages of 24 and 33 months contributed to variance in children's word type growth over and above the effect of maternal word types, as well as on an independent measure of receptive vocabulary at 54 months. We discuss possible mechanisms by which expansions can play an important role in vocabulary development.